Green assessment criteria: Perception among key industrial players' towards Stadium Retrofit in Malaysia / Syed Nabil Imran Syed Abdul Hafiz and Asniza Hamimi Abdul Tharim - Syed Abdul Hafiz, Syed Nabil Imran; Abdul Tharim, Asniza Hamimi (2020)
In the current era, the term Green Building is widely known seemingly across the continent by vast organizations with the objective to preserve the world's resources. Organizations introduce the Green Rating Tools tallying and to be used to verify the applications of sustainable criteria towards a building or perhaps a township. Several categories were divided to indicate the types of building comprising new building or existing building, residential building or non-residential building, industrial building or township. The retrofit concept is often used towards heritage building to preserve and protect the history gazette for the future generations. The concept was also applicable for the stadium whilst European had already implemented the concept and received Green Building Certificate by the councils. On the contrary, the stadium in Malaysia was not yet ready to begin implementing the retrofitting concept. The understanding of the green assessment criteria is already being measured within the key industrial players. Consequently, the,selection of the criteria by the key industrial players will determine the stadium retrofitting project will be a success achieving Green Building Certificate.